The adventures of Daniel Boom, a.k.a. Loud Boy. [1], Sound off! - Steinberg, David, 1962- (Grosset & Dunlap, 2008)
Daniel Boom, a kid with no volume control, becomes Loud Boy and fights the Kid-Rid Corporation, which has silenced the world with a machine called the Soundsucker LX.